Pengaruh Toleransi Sosial Terhadap Studi Tentang Persepsi dan Praktik Dalam Membangun Harmoni Sosial di Kalangan Mahasiswa Jurusan Pendidikan Antropologi Unimed - Sitorus, Nurainun; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Siregar, Umar Haddad; Salsabila, Sabrina; Situmorang, Widia Febiola (Indonesian Journal of Education and Development Research, 2025)
Social tolerance plays an important role in building a harmonious environment so that it can increase academic and social activities on campus. This practice of tolerance also plays a role in influencing the comfort of Unimed anthropology education students to carry out education in their environment. This study uses a qualitative data collection method with interviews and observations with 5 respondents of anthropology education students in batches 2022, 2023, 2024. This study aims to examine the influence of social tolerance on the study of perceptions and practices in building social harmony among Unimed Anthropology Education Students. The results of the study show that social tolerance has developed well in the academic environment through courses that discuss cultural diversity and the role of lecturers in forming an open attitude towards differences. However, there are still challenges such as the tendency to form groups based on ethnic, religious, or lifestyle similarities, as well as stereotypes that hinder academic discussions. The practice of tolerance is seen in everyday interactions, such as cooperation between students across religions in group assignments, respect for religious celebrations, and active participation in student organizations.